EVIDENCE FOR LITHOSPHERIC DETACHMENT IN THE CENTRAL ANDES FROM LOCAL EARTHQUAKE TOMOGRAPHY - Schurr B.; Rietbrock A.; Asch G.; Kind R.; Oncken O. (My University, 2006)
Data from three temporary seismic networks were merged for tomographic inversion. Although the deployments did not coincide in time, spatial overlap was achieved by re-occupying existing sites. Travel times and t⁎ operators of about 1600 earthquakes were inverted for 3D models of νp, νp/νs and P-wave attenuation (Qp−1). All three attributes provide a consistent image of the entire subduction zone on a lithospheric scale. The tomographic images reveal low velocities and high attenuation in the crust and mantle underlying the Western Cordillera and most of the Puna plateau, indicative of weak rheology and mostly asthenospheric mantle. In contrast, forearc and eastern foreland are characterized by high Qp values, corresponding to cold temperatures in accordance with thermal models. In the backarc, between 23°S and 24°S, a high velocity, high Qp structure beneath the Eastern Cordillera and eastern Puna is interpreted as detaching continental lithosphere that has been thickened in the orogenic process. South of this structure, the mantle is characterized by low velocities, high νp/νs ratios, and low Qp values. Here it is believed that lithosphere originally underlying Andean crust has already been removed. This is supported by new estimates of crustal thickness and volcanic activity.